Internal Structure and Invariance of a Brief Version of the Marijuana Motives Measure (MMM-P15) in a Peruvian Population of Marijuana users - Vallejos-Flores, Miguel; Capa-Luque, Walter; Caycho-Caja, Aaron; Chavez Santamaria, Alexandra; Reyes-Baca, Gino; Bello-Vidal, Catalina (Anales de Psicología / Annals of Psychology, 2023)
Background: The identification of the reasons for marijuana use has been supported by instruments such as the MMM. Despite its importance, there are still no valid brief versions of this instrument in Latin American countries. This paper seeks to fill this gap by providing evidence of validity and reliability, as well as the structural invariance of the MMM. Method: The sample consisted of 1164 male and female marijuana users, aged between 18 and 49 years, from Lima and Callao. Results: The factor analysis found a pentafactorial structure. The brief version (MMM-P15) and the wide MMM showed favorable properties from structure and reliability (ꙍ > 0.88, H > .84) with a slight superiority of the short instrument (RMSEA = .058 [CI 90% .050, .067], SRMR = 0.044, TLI = 0.99, CFI = 0.99). Likewise, both versions maintain the invariance of the instrument according to sex and evidence of internal validity was found (AVE > 0.50). Conclusions: The MMM-P15 shows psychometric properties that support its use in both male and female marijuana users, and it is a short, versatile, and useful instrument for research purposes even in clinical settings.